PENGARUH MAINTENANCE COSTS DAN NET WORKING CAPITAL TERHADAP REVENUE PADA PERUSAHAAN SEKTOR TRANSPORTASI DAN LOGISTIK YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Ade Pipit Fatmawati; Devi Masyithoh Amanda Nurafiyah Yasmin Maheswari (LAND JOURNAL, 2026)
Transportation and logistics companies play the crucial role for supporting Indonesia's economic to growth. Companies need to maintain their business performance to remain competitive and profitable. One way to maximize revenue is by managing maintenance costs and increasing working capital. The purpose research to analyze effect maintenance costs and net working capital on revenue in transportation and logistics companies listed on Indonesia Stock Exchange (IDX). Results of study are expected be used study material for further scientific development, particularly regarding the effect of maintenance costs and net working capital on revenue. Research method used quantitative method with purposive sampling technique. The sample used financial statements of transportation and logistics companies for four periods (2021-2024). Tests were conducted using Normality Test, Product Moment Correlation Analysis, Multiple Correlation Analysis, Multiple Regression Analysis, T-Test (Partial), F-Test (Simultaneous), and Coefficient of Determination Test using IBM SPSS Statistics 25. The t-test results indicate that maintenance costs have a partial positive and significant effect on revenue, and net working capital has a partial positive and significant effect on revenue. The results of the f-test show that maintenance costs and net working capital simultaneously have a positive and significant effect on income.